2017
DOI: 10.1016/j.dnarep.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase β: A missing link of the base excision repair machinery in mammalian mitochondria

Abstract: Mitochondrial genome integrity is fundamental to mammalian cell viability. Since mitochondrial DNA is constantly under attack from oxygen radicals released during ATP production, DNA repair is vital in removing oxidatively generated lesions in mitochondrial DNA, but the presence of a strong base excision repair system has not been demonstrated. Here, we addressed the presence of such a system in mammalian mitochondria involving the primary base lesion repair enzyme DNA polymerase (pol) β. Pol β was localized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 77 publications
1
69
0
Order By: Relevance
“…Previous studies showed that POL β stability may depend on interactions with XRCC1 [4143], and XRCC1 localization has been previously observed to be primarily nuclear [26]. POL β functions in both nuclear and mitochondrial BER and is observed within the cytoplasm, mitochondria, and nucleus of cells [27, 44].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that POL β stability may depend on interactions with XRCC1 [4143], and XRCC1 localization has been previously observed to be primarily nuclear [26]. POL β functions in both nuclear and mitochondrial BER and is observed within the cytoplasm, mitochondria, and nucleus of cells [27, 44].…”
Section: Resultsmentioning
confidence: 99%
“…However, the TNBC cells also showed altered localization of POL β that did not correlate with altered XRCC1 localization. The MDA-157 and MDA-231 cells showed low nuclear content of POL β, whereas HCC1806 and MDA-468 showed nuclear POL β enrichment [27, 44]. Loss of POL β does not induce the same level of hypersensitivity to DNA damaging agents as loss of XRCC1 [52, 62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Transcription of mtDNA is initiated at one of three promoter regions, two located on the heavy strand (HSP1 and HSP2) and one located on the light strand (LSP), where an overwhelming majority of transcripts are produced by transcription from HSP1 ( Fig. Only 7 of the 11 known DNA glycosylases that initiate BER have been identified in the mitochondria and recently, evidence presented by the Wilson and Bohr groups indicated that the resynthesis step after damage removal can be performed by DNA polymerase beta during repair of mtDNA (Prasad et al, 2017;Sykora et al, 2017;reviewed in Prakash and Doublié, 2015). Of the mitochondrial transcription components, TFAM appears to be regulated via post-translational modifications, where the precise implications of these modifications on epigenetic regulation of mitochondrial transcription are unknown (Lu et al, 2013;King et al, 2018).…”
Section: Mtdna Replicationtranscription and Repairmentioning
confidence: 99%
“…For instance, the base excision repair (BER) pathway appears to be the most abundant pathway within the mitochondria and repairs small, nonbulky lesions such as alkylated and oxidized DNA bases (reviewed in Prakash and Doublié, 2015;Saki and Prakash, 2017). Only 7 of the 11 known DNA glycosylases that initiate BER have been identified in the mitochondria and recently, evidence presented by the Wilson and Bohr groups indicated that the resynthesis step after damage removal can be performed by DNA polymerase beta during repair of mtDNA (Prasad et al, 2017;Sykora et al, 2017;reviewed in Prakash and Doublié, 2015). Various proteins involved in homologous recombination and translesion DNA synthesis have also been identified within the mitochondria (Sage et al, 2010;Dmitrieva et al, 2011;García-Gómez et al, 2013;Singh et al, 2015).…”
Section: Mtdna Replicationtranscription and Repairmentioning
confidence: 99%
“…Recent reports have shown the presence of the major nuclear BER DNA polymerase, DNA polymerase β (Polβ), in mitochondria in the brain [65,76], with a likely role in mtDNA repair. 3xTgAD mice with a 50% reduction of Polβ (3xTg AD/Polβ +/− ), which also contain a mutated version of human tau, display exacerbated AD phenotypes with impaired cellular bioenergetics and mitochondrial dysfunction [58,77].…”
Section: Introductionmentioning
confidence: 99%